2022
DOI: 10.3389/fcimb.2022.926352
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Profile of Procoagulant Extracellular Vesicles Reflects Complement System Activation and Platelet Hyperreactivity of Patients with Severe COVID-19

Abstract: BackgroundExtracellular vesicles (EVs) are a valuable source of biomarkers and display the pathophysiological status of various diseases. In COVID-19, EVs have been explored in several studies for their ability to reflect molecular changes caused by SARS-CoV-2. Here we provide insights into the roles of EVs in pathological processes associated with the progression and severity of COVID-19.MethodsIn this study, we used a label-free shotgun proteomic approach to identify and quantify alterations in EV protein ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…In addition, White et al [37] who investigated the TFPI values in platelet-poor plasma of noncritical and critical COVID-19 patients (as defined by WHO criteria), found that critical patients had significantly elevated TFPI compared with noncritical patients. In accord, Moraes et al ., who isolated plasma extracellular vesicles from healthy donors and patients with severe COVID-19 and employed a proteomic approach to discern variations in extracellular vesicle protein abundance, notably observed the exclusive presence of TFPI within the proteome of nonsurvivors [38]. In addition, Corey et al [35] also observed an association between the elevation of TFPI levels and the acute respiratory distress syndrome (ARDS) severity in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, White et al [37] who investigated the TFPI values in platelet-poor plasma of noncritical and critical COVID-19 patients (as defined by WHO criteria), found that critical patients had significantly elevated TFPI compared with noncritical patients. In accord, Moraes et al ., who isolated plasma extracellular vesicles from healthy donors and patients with severe COVID-19 and employed a proteomic approach to discern variations in extracellular vesicle protein abundance, notably observed the exclusive presence of TFPI within the proteome of nonsurvivors [38]. In addition, Corey et al [35] also observed an association between the elevation of TFPI levels and the acute respiratory distress syndrome (ARDS) severity in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Besides TF, exosomes from COVID-19 patients have been shown by proteomic analysis to convey pro-inflammatory cargo that was effective in triggering inflammatory responses in cells of distant organs [45]. Generally, the proteome of EVs in COVID-19 shows abnormalities, such as complement activation and platelet hyperreactivity [46], and increased loads of vWF, UPAR, and ADAMTS13 that correlates with higher levels of the thrombotic marker, D-dimer, and increased disease severity. In our study, vWF was shown to be upregulated as an EV component under 0-21% O 2 but downregulated under 95% O 2 and it may also have an important impact on pro-coagulative activity of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, high concentrations of TF-bearing EVs in circulation correlate with disease severity and occurrence of thromboembolic events in severe COVID-19 patients, being proposed as a potential biomarker ( Guervilly et al, 2021 ). Platelets seem to be one of the main sources of TF-bearing circulating EVs during COVID-19, with severe patients presenting increased concentrations of platelet-derived EVs with higher surface expression of TF ( Moraes et al, 2022 ). Recently, we have reported the proteomic profile of circulating EVs from COVID-19 patients reflecting increased platelet degranulation, complement activation and fibrin clot formation ( Moraes et al, 2022 ).…”
Section: Platelets Drive Pacs-associated Hypercoagulabilitymentioning
confidence: 99%
“…Platelets seem to be one of the main sources of TF-bearing circulating EVs during COVID-19, with severe patients presenting increased concentrations of platelet-derived EVs with higher surface expression of TF ( Moraes et al, 2022 ). Recently, we have reported the proteomic profile of circulating EVs from COVID-19 patients reflecting increased platelet degranulation, complement activation and fibrin clot formation ( Moraes et al, 2022 ). A similar profile of circulating EVs was found to persist in individuals with PACS in our recent study.…”
Section: Platelets Drive Pacs-associated Hypercoagulabilitymentioning
confidence: 99%